Legal Sustainability Of Object Gadai Execution By A Porrietary Assets That Are Debt Guaranteed Without Agreement Of Husband Or Wife (Study At PT. Pegadaian in Medan City) - Yose Rizal Efendi; Ramlan Ramlan; Ferry Susanto Limbong (Veteran Law Review, 2022)
As a marriage bond progresses, there will certainly be tests or trials that come, especially economic problems, of course the husband as the head of the household is the burden of responsibility in providing for his wife both physically and mentally, in this day and age one of the ways that is often taken in solving problems economy is by using bank facilities as referred to in Article 1 point 2 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking, which states that a bank is a business entity that collects funds from the public in the form of savings and distributes it to the public in the form of credit. and or other forms in order to improve the lives of many people. The type of research used in this research is normative legal research. This type of research was chosen because the study in this study is a study of legal science, therefore it must be studied from its legal aspects. Normative legal research is research on library materials (secondary data) that are relevant to the problems to be analyzed, both in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Legal certainty for the legal arrangement of the object of a pledge which is a joint asset in a marriage which is used as a debt guarantee without the consent of the husband or wife is contained in Article 1 of Law Number 1 Year 1974 concerning Marriage and Article 119 of the Civil Code Kemdian Article 36 paragraph (1) of Law No. 1 of 1974 concerning Marriage has actually provided a legal corridor, that the action to carry out a pledge in the form of joint assets obtained during the marriage period must be based on an agreement between the two parties between the husband and wife. The process of executing the object of the pledge in the form of marital assets which is used as collateral for debt without the consent of the husband or wife at PT. Pegadaian Medan City, first PT. Pegadaian Medan City conveyed that the debtor is due for payment which will be sent via an official letter from PT. Mortgage of Medan City, then starting 7 (seven) days after the official notification to the debtor, there is also no good faith of the debtor in paying the debt bill, so PT. Medan City Pegadaian conducts an auction for the object of the pawn in the form of joint assets of the marriage bond